Effect of creatine on swimming velocity, body composition and hydrodynamic variables - Silva, A. J.; Machado Reis, V.; Guidetti, L.; Bessone Alves, F.; Mota, P.; Freitas, J.; Baldari, C. (The Journal of Sports Medicine and Physical Fitness, 2007)
Aim: Creatine supplementation (CS) has been reported to increase body weight and improve performance during high intensity, short duration, exercise tasks. However, none of the published studies has investigated the influence of CS on performance related hydrodynamic variables during swimming. To investigate the effect of oral CS on swimming velocity, body composition and hydrodynamic variables during the period of final preparation of competitive junior female swimmers. Methods: In a double blind and randomized manner, 16 female swimmers, were supplemented with 20 g day-1 of creatine monohydrate (CS group), or a maltodextrin placebo (PL group) for 21 days. Just pre- and post-21 days of supplementation, subjects performed 2¥25 swimming bouts at maximum velocity with a 3 min recovery between bouts. The variables measured were 25 m swimming velocity (MSV25); active drag force (Df); hydrodynamic coefficient (Cx); power output (Po). Body measures were also analysed: body weight (kg), fat-mass (% FAT), body water (% H2O), and fat free mass (FFM). Results: Significant differences were observed in hydrodynamic values: the CS group showed a significant reduction (ª25%), in Df, Cx and Po values, when comparing pretest with post-test. No differences were found in variables related to body composition and performance between CS group and PL group, as well as for CS group during the experimental period. Conclusion: These data suggest that 21 days of CS produced significant effects on gross and/or propelling efficiency during swimming in female athletes. However, CS did not influence performance, body weight and body composition.